How quantitatively important are shocks to consumption and income tax rates for business cycle fluctuations? Lessons from Bulgaria (1999-2020) - VASILEV, Aleksandar (Journal of Mathematical Economics and Finance, 2024)
This paper analyzes the macroeconomic effects of fluctuations in the marginal tax rates of consumption and income. To this end, stochastic tax rates are introduced as in Braun (1992), into a real-business-cycle setup augmented with a detailed government sector. The model is calibrated to Bulgarian data for the period following the introduction of the currency board arrangement (1999-2020). The quantitative importance of the presence of stochastic taxation is investigated for the stabilization of cyclical fluctuations in Bulgaria. The quantitative effect of such shocks to the marginal tax rates is found to be very small, and thus not important for either business cycle stabilization, or public finance issues.